PENGARUH NIM, BOPO, LDR, CAR, CR DAN DPK TERHADAP ROA PADA BANK KONVENSIONAL YANG TERDAFTAR DI BEI PERIODE 2013 - 2015 - Theodorus Agung Nurhana, 14.05.62.0008; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This research aims to examine and analyze the effect of NIM, BOPO,  LDR, CAR, CR, deposits on ROA in conventional banking company in period 20132015. The population in this research are all banking companies listed on the Indonesian Stock Exchange in period 2013-2015. Sampling technique used is purposive sampling with certain criteria. The data in this study were analyzed using multiple linear regression. The results showed that there NIM and CR have positive effect on ROA, BOPO has negative effect on ROA, LDR does not have negative effect on ROA, CAR and DPR does not positive effect on ROA.    Keywords: NIM, BOPO, LDR, CAR, CR, DPK, ROA